Effect of Ti content and nitrogen on the high-temperature oxidation behavior of (Mo, Ti)5Si3. (November 2017) - Azim, M.A.; Gorr, B.; Christ, H.-J.; Lenchuk, O.; Albe, K.; Schliephake, D.; Heilmaier, M.
Abstract: The binary intermetallic compounds Mo5 Si3 (T1) and Ti5 Si3 are prone to rapid oxidation below 1000 °C. Recent investigations on (Mo, Ti)5 Si3, however, revealed that macro-alloying with 40 at.% Ti can result in a very good oxidation resistance in a wide temperature range (750–1300 °C) due to the formation of a duplex layer composed of a silica matrix with dispersed titania. Additionally, Ti decreases density making (Mo, Ti)5 Si3 a promising key constituent of quaternary Mo-Si-B-Ti alloys considered for ultrahigh temperature structural applications. The aim of this study is to obtain an in-depth understanding of the influence of different Ti concentrations as well as of nitrogen on the oxidation behavior of (Mo, Ti)5 Si3 at intermediate and elevated temperatures. The microstructure and oxidation mechanisms were analyzed using various experimental techniques. The experimental results were supported by ab initio and thermodynamic calculations. Highlights: Ti macroalloying results in fast passivation of Mo5 Si3 (T1) at 750–1300 °C. Oxidation resistance results from the SiO2 matrix with embedded TiO2 particles. Ti affects migration barrier of Mo/Si. Ti depleted T1 is more stable than Si depleted. Slight Si concentration increase stabilizes a two-phase field SiO2 -T1. N2 in the test atmosphere causes increased oxidation of Mo37.5Si40Ti.